2014
DOI: 10.1186/1471-2474-15-357
|View full text |Cite
|
Sign up to set email alerts
|

Algogenic substances and metabolic status in work-related Trapezius Myalgia: a multivariate explorative study

Abstract: BackgroundThis study compares the levels of algesic substances between subjects with trapezius myalgia (TM) and healthy controls (CON) and explores the multivariate correlation pattern between these substances, pain, and metabolic status together with relative blood flow changes reported in our previous paper (Eur J Appl Physiol 108:657–669, 2010).Methods43 female workers with (TM) and 19 females without (CON) trapezius myalgia were – using microdialysis - compared for differences in interstitial concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 87 publications
(130 reference statements)
2
9
0
Order By: Relevance
“…The association between TBF and neck pain in the present study indicates that muscle microcirculation and alternations in TBF may be involved in the pathogenesis of neck pain development, which is also consistent with previous studies (Gerdle et al 2014;Knardahl 2002;Larsson et al 2008;Larsson et al 1999;Näslund et al 2007;Rosendal et al 2004;Sjogaard et al 2010;Strøm et al 2009b;Thorud et al 2012). Strom et al (2009b) showed significant correlations between neck pain and TBF during computer work for both subjects with chronic neck and shoulder pain and a healthy reference group; however, the associations were in opposite directions in the two groups.…”
Section: Neck Pain and Trapezius Blood Flowsupporting
confidence: 92%
“…The association between TBF and neck pain in the present study indicates that muscle microcirculation and alternations in TBF may be involved in the pathogenesis of neck pain development, which is also consistent with previous studies (Gerdle et al 2014;Knardahl 2002;Larsson et al 2008;Larsson et al 1999;Näslund et al 2007;Rosendal et al 2004;Sjogaard et al 2010;Strøm et al 2009b;Thorud et al 2012). Strom et al (2009b) showed significant correlations between neck pain and TBF during computer work for both subjects with chronic neck and shoulder pain and a healthy reference group; however, the associations were in opposite directions in the two groups.…”
Section: Neck Pain and Trapezius Blood Flowsupporting
confidence: 92%
“…In office workers the painful muscles showed adverse functional, morphological, hormonal, as well as metabolic characteristics. 28 , 29 , 30 , 31 , 32 Metabolic muscular capacity increased 33 as demonstrated even at the gene level, 34 and muscle morphological recovery was documented using advanced immunohistochemical stainings for satellite cells 35 and neuronal nitric oxide synthase. 28 …”
Section: Resultsmentioning
confidence: 99%
“…There may of course be some false positives among our findings, but all in all it does not seem sensible to dismiss all our results as a gigantic type I error. The MVDA methodology used in the present study is the same as used by the Linköping group in a number of recent peer-reviewed publications in different journals,22,29,6266 and it is congruent with the principles argued for by Wheelock and Wheelock 28. Finally, in order to ensure the robustness of our statistical methodology, the CSF data of the present study were recomputed using the statistical methodology described by Moen et al32 (with use of false discovery rate); the result of this recomputation was exactly the same as the list presented in Table 1 (TG being the last author of both articles).…”
Section: Discussionmentioning
confidence: 99%